Public Service Communication of PT Angkasa Pura II in Increasing Customer Satisfaction at H.A.S Hanandjoeddin Belitung Airport - Adelia Febrianda; Muhammad Najih Farihanto (Jurnal Indonesia Sosial Teknologi, 2024)
This research was conducted to find, describe, and explain about public service communication of PT. Angkasa Pura II Airport H.A,S Hanandjoeddin Belitung. The research method used is a descriptive qualitative research method. The data was obtained from the results of documentation studies, observations, and in-depth interviews with the staff of the authorized H.A.S Hanandjoeddin Belitung Airport. The results of this study show that public service communication carried out by H.A.S Hanandjoeddin Belitung Airport staff has been running well, but still needs improvement in terms of available facilities. The conclusion of the quality of service at H.A.S Hanandjoeddin Belitung Airport has covered five main aspects, namely physical evidence, reliability, responsiveness, guarantee, and attention, but still needs improvement in some facilities. In terms of physical evidence, the narrow waiting room facilities, lack of seats, and unavailability of garbarata make passengers comfortable, so the improvement of these facilities is important.